Қарақалпақ халық дәстаны «Едиге»де алғыс, пәтия ҳәм тилеклердиң қолланылыў өзгешелиги - Абдимуратов, Л.А (SCIENCE and SOCIETY, 2025)
The article gives data on gratitude, in the “Ediga” of the Karakalpak folk epic. Here, the features and
Keywords: fundamental; material; form; episode; gratitude; blessing